Child-Friendly School Indicators in Primary Education: Implications for the Implementation of Gender Equality Approach - Endah Hendarwati; Holy Ichda Wahyuni (International Journal of Educational Research & Social Sciences, 2026)
This study aims to analyze the indicators of Sekolah Ramah Anak (SRA)/Child-Friendly Schools (CFS) in primary education and examine their implications for gender equality content. The study is grounded in the observation that the SRA framework generally emphasizes safety, protection, participation, health, and inclusiveness, yet has not adequately integrated gender as an explicit analytical dimension. In fact, the primary school environment constitutes an important space for shaping children’s social experiences, including gender relations, participation, self-expression, and access to equitable learning spaces. This study employed a qualitative approach using a systematic literature review design. Data were collected through a review of academic databases and relevant policy documents, and were analyzed using thematic analysis combined with a critical gender lens. The findings indicate that the dominant SRA indicators include safe and protective environments, anti-discriminatory practices, child participation, health and well-being, and inclusive education. However, most of these indicators are still formulated in neutral terms and remain insufficiently sensitive to capture gender-based inequalities in children’s school experiences. Further analysis reveals that gender bias may manifest in teaching practices, classroom participation patterns, the use of school facilities, and social relations that shape children’s experiences differently. Therefore, this study recommends the reconstruction of SRA indicators to make them more explicit, contextual, and transformative by positioning gender equality as a cross-cutting principle embedded in school policy, governance, infrastructure, participation, and pedagogical practices in primary education. These findings affirm that a truly child-friendly school is not only administratively safe, but also experientially just for all children.